Analysis of Community Leaders' Participation in the Implementation of the Environmental Security Care Movement Program in Kolam Village, Percut Sei Tuan District - syahfitri, Ratih; Yusnadi (Journal of Nonformal Education and Community Empowerment, 2025)
This study aims to analyze the Participation of Community Leaders in the Implementation of the Environmental Security Care Movement Program (GPKL) in Kolam Village, Percut Sei Tuan District. This study uses a qualitative descriptive method. The subjects in this study were 4 people consisting of the Village Head, Hamlet Head, Karang Taruna, and Traditional Leaders. Data collection used interview, observation and documentation techniques. Data analysis techniques used data reduction, data presentation and drawing conclusions. Data validity used source triangulation and method triangulation. The results of the study show that the participation of community leaders in caring for environmental security (GPKL) is: (1) material participation that includes money participation, and property/object participation, (2) non-material participation that includes thought participation, skill participation, and energy participation.